2005
DOI: 10.1002/ejoc.200500558
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photophysical Studies of New Porphyrin–Phthalocyanine Dyads with Hindered Rotation

Abstract: A series of novel porphyrin-phthalocyanine (Por-Pc) dyads 1-3 have been synthesized by using standard methodologies for unsymmetrically substituted phthalocyanine preparation. These two chromophoric units have been directly linked for the first time, that is, without any spacer, through the β-pyrrolic position of a meso-tetraphenylporphyrin, thus allowing a close proximity of the two units in a rigid arrangement. For this, a novel porphyrin-phthalonitrile precursor 4 had to be prepared. The UV/Vis spectra indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In the recent time the synthesis and photophysical investigations of some porphyrin (P)-phthalocyanine dyads have been reported [26][27][28][29][30][31]. It was found, that in most cases, an efficient photoinduced energy transfer from initially photoexcited P moiety to the Pc unit occurs.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent time the synthesis and photophysical investigations of some porphyrin (P)-phthalocyanine dyads have been reported [26][27][28][29][30][31]. It was found, that in most cases, an efficient photoinduced energy transfer from initially photoexcited P moiety to the Pc unit occurs.…”
Section: Introductionmentioning
confidence: 99%
“…New and highly efficient synthetic routes have generated many porphyrin-like compounds with unique characteristics for their uses in several other applications such as oxidative catalysis [ 209 , 210 ] and as biomimetic model systems of the primary processes of photosynthesis [ 211 , 212 ]. Presently, the interest also includes the supramolecular units, namely molecular recognition in chemical receptors and sensors [ 213 215 ], as light-harvesting devices [ 216 219 ] and as materials for advanced technologies, mainly in nanosciences [ 220 , 221 ]. Nevertheless, the photodynamic treatment is certainly the most promising application of porphyrin-like compounds.…”
Section: Photodynamic Therapy: a New Antimicrobial Approach To Infmentioning
confidence: 99%
“…DFT studies allowed us to justify the differences observed on the site selectivity of successive 1,3-dipolar cycloadditions to meso-tetraarylporphyrins [14]. We have also reported the synthesis of [1,2,3]-triazolo[4,5-b]porphyrins, including the single crystal X-ray diffraction of a porphyrin pentamer [15] and the synthesis and photophysical studies of porphyrinphthalocyanine dyads with hindered rotation [16].However, by far the most important publication in relation with the present paper is one by Okuno et al [17]. These authors calculated at the B3LYP/6-31G(d) level the rotation barrier about the phenyl-porphyrin 1 and the ortho-methoxyphenyl-porphyrin 2 bonds (Fig.…”
mentioning
confidence: 95%
“…DFT studies allowed us to justify the differences observed on the site selectivity of successive 1,3-dipolar cycloadditions to meso-tetraarylporphyrins [14]. We have also reported the synthesis of [1,2,3]-triazolo[4,5-b]porphyrins, including the single crystal X-ray diffraction of a porphyrin pentamer [15] and the synthesis and photophysical studies of porphyrinphthalocyanine dyads with hindered rotation [16].…”
mentioning
confidence: 96%